Zastosowanie zbiorów przybliżonych do oceny popularności wykładów ze statystyki matematycznej - Machowska-Szewczyk, Małgorzata; Sompolska-Rzechuła, Agnieszka (Use of Rough Sets to Estimate the Popularity of Lectures on Mathematical Statistics, 2007)
One of the factors influencing the popularity of lectures on mathematical statistics al third level institutions is the personality of the lecturer. How can we measure the human factor called "charisma", the vocation to work as a professional lecturer? In this article, a method of evaluating that factor is presented, based on elements of rough sets. This concept of evaluating a lecturer's charisma is based on the comparison of students' attendance at a lecturer's classes, compared to students' attendance at other lecturers' classes for similar subjects. The person whose lectures have above average attendance can be recognised as a lecturer with charisma.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 141-148